- #1

- 366

- 0

Reduce to the 2nd order and solve the eq.

(1-x^2)y'' - 2xy' + 2y = 0 (we know that y(1) = 0)

I don't know what to do here, except that I'm supposed to find y(2). I know the formulas

y(2) = y(1) Int(U) dx

where

U = (e^(-Int(p(x)dx)) / (y(1))^2

Can I use this?

(1-x^2)y'' - 2xy' + 2y = 0 (we know that y(1) = 0)

I don't know what to do here, except that I'm supposed to find y(2). I know the formulas

y(2) = y(1) Int(U) dx

where

U = (e^(-Int(p(x)dx)) / (y(1))^2

Can I use this?

Last edited: